1877 Nev. Stat. 88, ch 48, § 1, pt. 5. - (:unkn) unknown (General Publisher, 1877)
[t]o regulate the storage of gunpowder and other explosive or other combustible material.
--
Keywords: GUN POWDER STORAGE